English Language Learner education finance scholarship: An introduction to the special issue - Oscar Jiménez-Castellanos (Arizona State University, 2017)
In this article, I introduce the special issue on education finance and English Language Learners, with the purpose to disseminate timely and relevant education finance scholarship with a particular focus on English Language Learners (ELLs).Here, I provide an analytical argument for why this topic is of great importance for our educational system and policy, yet it remains especially understudied. Next, I provide a brief overview of the previous ELL school finance literature. Then I outline the four scholarly papers included within this special issue, noting each paper's contributions to our knowledge base and implications for policy. I conclude by pointing to further scholarship based on articles in this special issue.